What is the burden of tinnitus? - Pryce, Helen; Dauman, Nicolas; Burns-O’Connell, Georgina (Frontiers in Psychology, 2023)
Introduction Tinnitus is a complex experience that often occurs alongside other health conditions, including hearing loss. In the UK, as in other western countries, patterns of health are changing with a rise in multi-morbidity and complexity of health conditions. As we age, we can expect to live with multiple health conditions. Burden of illness has long been recognised. Less well recognised is the burden that accumulates from the treatment of health conditions. Methods This qualitative thematic analysis of patient accounts described the cumulative burdens of tinnitus, both the experience of hearing the tinnitus and from the treatments undertaken. Between 2017-8 we conducted interviews with 38 participants who were help-seekers in a range of contrasting UK clinical services (Physician led, Audiology led and Hearing Therapy led). We examined these interview data using reflexive thematic analysis methods to identify and explore the cumulative burdens for those who live with and seek help for their tinnitus. Specifically, we used six phased approach to determine and group themes. Results The themes provide a coherent description of the nature of the burden that people with tinnitus experience. Discussion In tinnitus, as with most chronic health conditions, the largest treatment workload is devolved to the patient. Patients are required to implement treatments, learn about tinnitus and find new ways of coping. Yet this work happens invisibly, without recognition from clinicians who measure outcomes but not the efforts made to achieve outcomes. Patient-centred care depends upon the recognition of the cumulative burdens that patients experience.